A pilot study on sperm DNA damage in β-thalassemia major: is there a role for antioxidants? - Elsedfy, Heba; De Sanctis, Vincenzo; Ahmed, Alaa Youssef; Mohamed, Noha Refaat; Arafa, Mohamed; Elalfy, Mohsen Saleh (Acta Biomedica Atenei Parmensis, 2018)
Excess iron deposition in patients with beta thalassemia major (BTM) causes excess free radical formation, damages the hypothalamic pituitary testicular axis and production of sperms with DNA defects. As antioxidants were reported to improve fertility in healthy males; their effectiveness to improve sperm DNA defects in adult males with BTM was studied. Twenty fully pubertal BTM patients were included consecutively, all had semen analysis; 10 were found to be azoospermic, so further analysis for sperms and DNA defects was conducted on the remaining 10 participants. Semen was analyzed for antioxidants in seminal plasma and sperms for defects including the DNA fragmentation index, sperm deformity index, teratozospermia index and acrosomal index. Participants were then given L-carnitine and N-acetylcysteine for 6 months. All semen parameters were reassessed after treatment. The sperm deformity index and teratozospermia index increased significantly after treatment from 1.90±0.33 to 2.46±0.61 and from 1.59±0.22 to 1.86±0.28 respectively. So, apparently antioxidants accentuated sperm deformities in men with BTM. Therefore, the results of this study are not in favour with the use of antioxidants in BTM patients for improving potential fertility. Larger studies, however, are needed to confirm these preliminary results.